A Dynamic ID Assignment Mechanism to Defend Against Node Replication Attack in Static Wireless Sensor Networks - Mojtaba Jamshidi; Abdusalam Abdulla Shaltooki; Zahra Dagal Zadeh; Aso Mohammad Darwesh (Politeknik Negeri Padang, 2019)
One of the known dangerous attacks against wireless sensor networks (WSNs) is node replica. In this attack, adversary captures one or more normal nodes of the network, generates copies of them (replicas) and deploy them in the network. These copied nodes are controlled by the adversary which can establish a shared key with other nodes of the network easily and exchange information. In this paper, a novel algorithm is proposed to defend against this attack in static sensor networks. The proposed algorithm employs a multi-tree architecture to assign ID to the nodes dynamically and prevent attachment of the injected replica nodes to the network by the adversary. The efficiency of the proposed algorithm is evaluated in terms of memory, communication, and computation overheads and the results are compared with other existing algorithms. Comparison results indicate the superiority of the proposed algorithm in terms of mentioned measures. In addition, the proposed algorithm is simulated and its efficiency is evaluated in terms of probability of detecting replica nodes. Experiment results show that the proposed algorithm has favorable performance in detection of replica nodes.